Pulmonary function among flour mill workers: a systematic review and meta-analysis - Kuldip Upadhyay; Bhavani Shankara Bagepally; Rakesh Balachandar; Ankit Sheth; Ankit Viramgami (BMC Public Health)
Abstract Background Flour dust, with an inherent allergic nature, increases vulnerability to various respiratory ailments. We systemically reviewed and compared literature-reported pulmonary function parameters to quantify pulmonary dysfunction among individuals with high flour dust exposure (among flour mill workers) and relatively un-exposed groups. Methods Studies that compared pulmonary function parameters for flour dust exposed and unexposed control groups were systemically searched in PubMed, Scopus and Embase from inception to June 2024. The Newcastle Ottawa scale was used to assess the risk of bias among included studies. With the random effect model, we pooled (along with 95% CI) the mean difference for forced expiratory volume in the first second (FEV1), forced vital capacity (FVC), the ratio of FEV1 & FVC, mid-expiratory flow (FEF25-75%), peak expiratory flow rate (PEFR) and other pulmonary function parameters. Cochran-Q test and I 2 statistics were applied to determine heterogeneity. Results This quantitative synthesis included twenty-two studies involving 2,482 flour dust exposed and 1,925 control participants. The pooled mean difference for FEV1, FVC, FEV1/FVC, PEFR and FEF25 − 75% were − 0.43 L (-0.57, -0.29; I 2 = 88.7), -0.49 L (-0.64, -0.33; I 2 = 89.3), -3.5% (-6.49, -0.5; I 2 = 89.7), -1.36 L/s (-1.70, -1.03; I 2 = 90.4) and − 0.34 L/s (-0.63, -0.06; I 2 = 77.3). The pooled odds ratio for obstructive [12.9 (3.41, 49.2); I 2 = 82.4)] and restrictive changes [5.11 (0.55, 47.4); I 2 = 81.6] were significantly higher among the exposed than controls. As per the bias assessment majority of studies rated with moderate to severe risk of bias. Conclusion Study observed pulmonary function deficits associated with exposure to flour dust. However, considering the quality of primary studies and higher heterogeneity, high-quality larger studies with longitudinal design are required to affirm the effects of flour dust on lung function.